Analisis Laporan Keuangan Di Kantor Bappeda Kabupaten Lombok Barat - Baiq Reinelda Triyunarni; Dedy Iswanto; Abdul Hafiz (UNIVERSITAS MUHAMMADIYAH MATARAM, 2021)
This research is entitled Analysis of Financial Statements at the Bappeda Office of West Lombok Regency. The purpose of this study is to find out the 2017-2019 Bappeda Lombok Barat Report using the Liquidity and Solvency ratio. Financial statements are information that describes the financial condition of a company and furthermore this information can be used as a description of the company's performance. Analysis of financial statements in public sector organizations is done by comparing the financial performance of one period with the previous period based on financial statements, there are various types of ratios, namely liquidity ratios, solvency ratios, activity ratios, probability ratios, and growth ratios. The method used in this research is quantitative-qualitative using a deductive approach and analysis using Liquidity Ratios and Solvency Ratios, the current ratio of the Regional Development Planning Agency Office for 2017-2019 shows that in 2014 the current ratio was 667.50% in 2018 it decreased to 592.62 % or (74.88%) then experienced a significant increase in 2019 by 932.84% or an increase of 340.22%. Quick Ratio/Quick Ratio 2017 Quick Ratio/Quick Ratio of 264.91% in 2018 decreased by 170.31% or by 94.61% and then experienced a significant increase in 2019 by 524.25% or by 353.94%. In 2017-2019 based on Solvency Ratio analysis, in 2017-2019 the West Lombok Regional Development Planning Agency was able to pay all its debts then in 2019 it decreased by 0.02 and an average of 0.09%. The results of the calculation of the debt ratio in 2019 decreased by 0.02 and an average of 0.09%.